Discourse in the digital age social media, power and society - Aiston, Jessica (Routledge critical studies in discourse, 2024)
"This collection makes the case for existing critical discourse analysis theory and methods to meaningfully engage with the new communicative parameters, power dynamics, and technological affordances of contemporary digital spaces. The volume lends a critical focus on discursive practices operating through the paradigm of social media communication, arguing that the critical discourse social media research must go beyond the notion of the simple analysis of social media data. The volume features chapters highlighting a diverse range of methods, including multi-sited ethnography, multimodality, argumentation, and topic modelling, as applied to a global range of case studies to present a holistic portrait of the latest methodological and theoretical debates in this space. The book demonstrates the ways in which questions of identity run through these conversations and their subsequent re-shaping of existing societal discourse. In so doing, the collection advocates for a new tradition in critical discourse research, one which is rigorous in accounting for both solid discursive frameworks and the evolving complexity of digital platforms, to fully make sense of contemporary digital practices on the participatory web and advance the field forward. This book will be of interest to students and scholars in critical discourse studies, digital communication, media studies, and anthropology"